THE RELEVANCE OF MADRASAH TEACHER COMPETENCIES IN THE GENERATIVE AI ERA: TRANSFORMING THE ROLE FROM INFORMATION SOURCE TO FACILITATOR OF WISDOM - M. Kholil Tsamrotul Fuad; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The rapid development of Generative Artificial Intelligence (Gen-AI) has massively disrupted the educational landscape, sparking critical debates regarding the future relevance of the teaching profession. This article aims to assess the existence of madrasah teacher competencies in an era of instant digital information and to explore the empirical research gap that AI technology cannot replace. Utilizing a descriptive qualitative method with a conceptual study approach, this article analyzes the shifting paradigm of teaching in madrasahs. The findings indicate that while Gen-AI can provide cognitive information and scientific data within seconds, it possesses absolute limitations in the aspects of transferring values (transfer of values), spiritual guidance (tarbiyah), empathy, and moral role-modeling (uswatun hasanah). The competitive advantage of madrasah teachers lies in their transformative ability to shift from being mere "information sources" to becoming "facilitators of wisdom" (hikmah). Teachers play a vital role in guiding students' morals, fostering critical thinking, and contextualizing instant knowledge from AI with noble character values (akhlak karimah). The conclusion affirms that the role of madrasah teachers remains absolutely relevant in the AI era, provided there is a reorientation of competencies focusing on strengthening affective-spiritual aspects and adaptive technological literacy.